2012
DOI: 10.1111/j.1747-1567.2012.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiaxial Testing of Materials Using a Stewart Platform: Case Study of the Nooru-Mohamed Test

Abstract: A first application of a Stewart platform used as a multiaxial testing machine is presented. A specific case study is chosen, namely the so‐called Nooru‐Mohamed experiment, which is a tension‐shear test on a notched concrete specimen. The calibration, analysis of performances, and a validation test are investigated. The results confirm that the hexapod can be used to apply multiaxial loadings under small displacements, and allow also the measurement of the six components of forces and torques. Additional digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…q = q 1 q 2 q 3 q 4 q 5 q 6 T represents the length of each actuated joint. Further details can be found in [11]. This machine is then used for the NM test, i.e.…”
Section: Loading Machinementioning
confidence: 99%
See 3 more Smart Citations
“…q = q 1 q 2 q 3 q 4 q 5 q 6 T represents the length of each actuated joint. Further details can be found in [11]. This machine is then used for the NM test, i.e.…”
Section: Loading Machinementioning
confidence: 99%
“…A first experimentation has been performed in [11] using the hexapod presented below in the case study of the NooruMohamed test. It revealed that an advanced control law is needed to use extra DOF to control boundary conditions.…”
Section: Experimental Setup and Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…These advantages indicate that 6-DOF parallel mechanisms are feasible to the applications of multi-dimensional material testing machines, and some related papers have been published. Nierenberger et al (2014) established a multi-axial testing machine and reproduced the Nooru-Mohamed test. Le Flohic et al (2014) studied the 3D control method to that test machine.…”
Section: Introductionmentioning
confidence: 99%